2020
DOI: 10.11591/ijece.v10i2.pp1641-1647
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for secured communication in wireless sensor networks

Abstract: Wireless sensor network (WSN) have limited bandwidth, low computational functions, energy constraints. Inspite of these constraints, WSN is useful where communication happens without infrastructure support. The main concern of WSN is the security as the sensor nodes may be attacked and information may be hacked. Security of WSN should have the capability to ensure that the message received was sent by the particular sent node and not modified during transmission. WSN applications require lightweight and strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The various schemes have been classified depending on the type of the encryption utilized as in Table 3. Symmetric encryption has the same key for encryption and decryption [49], [50]. The key must be transmitted securely between the sensor nodes.…”
Section: Packet Alteration Packet Injection and Packet Duplicationmentioning
confidence: 99%
“…The various schemes have been classified depending on the type of the encryption utilized as in Table 3. Symmetric encryption has the same key for encryption and decryption [49], [50]. The key must be transmitted securely between the sensor nodes.…”
Section: Packet Alteration Packet Injection and Packet Duplicationmentioning
confidence: 99%
“…On the other hand, a mathematical model-based approach has been developed to detect the malevolent intent of mobile agents in the event that they go rogue, in order to stop DoS assaults in vehicular ad hoc network (VANET) [30]- [34]. Considering this literature, many ensemble approaches have been suggested in recent works to address the problems with single classifiers [35]- [37]. Therefore, highly scalable and voting-based ensemble models were proposed [38]- [40].…”
Section: Figure 2 Overview Of Grey Hole Attack [19]mentioning
confidence: 99%
“…Such threats may be considered as one of the most important obstacles to the development of IoT [45], [46]. It is also observed that the optimal use of resources has received more attention over time [47], [48], and this is due to the development of wireless networks with limited resources, the Internet of Things, and the increasing use of sensors.…”
Section: Extraction Of Components 31 the Purposes Of Designing Cryptographic Algorithmsmentioning
confidence: 99%